PELATIHAN PENGGUNAAN MEDIA SOSIAL SEBAGAI LANGKAH PENCEGAHAN KEKERASAN TERHADAP PEREMPUAN DAN ANAK DI DESA PASIR GOMBONG - Apris Setyaningsih; M Fakhran Al Ramadhan (An-Nizam, 2022)
Violence against women and children has a number that tends to increase. Judging from the cases that are increasing every day. In preventing violence to woman and children the state and the people must prevent, protect, and take actions in accordance with the laws. This is the background for the author to make training related to the prevention of violence against women and children in the village of Pasir Gombong. Content creation training in the form of posters using Canva which will then be distributed in strategic places around the author's domicile and accompanied by education about violence against women and children. The purpose of this activity is through training on creating creative content on social media for young people, which is expected to help local communities participate in preventing violence against women and children. The implementation method is by using community education, training, and consultation.